LCH-Histiocytosis from Langerhans Cells in Craniofacial Region - M. Hubáček; J. Kozák (Czech Dental Chamber, 2005)
The authors retrospectively analyze the occurrence of histiocytosis from Langerhans cells (LCH) in a group of patients from the Children Stomatological Clinic in Prague - Motol from the years 1998-2003. There were 11 cases of LCH (6 boys and 5 girls) of the average age 5.4 years on the whole. In six cases the children suffered from monostotic form and in five cases there was the polyostitic form was determined. Attention was paid to the complexity of examined screening, unquestionable importance of histological examination. The possibility of LCH therapy is described. The authors prefer interdisciplinary collaboration in the diagnosis, therapy and dispensary care.